2008
DOI: 10.1097/ta.0b013e3181581f81
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxin Inhibits Heterotopic Ossification: An Experimental Study in Rabbits

Abstract: Levothyroxin demonstrated efficacy in preventing heterotopic ossification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Most of these models have variable repeatability, but the implantation of bone marrow to induce heterotopic bone formation can be demonstrated simply without the demand of time needed to prepare the material to be deployed. The induction procedure used in the present study was adopted from studies (5,10,11) that have documented that 35 days are sufficient for heterotopic bone formation in the quadriceps of rabbits following implantation of 2 mL BM collected from the iliac crest of the animal. Namazi and Mozaffarian (5) observed that after 35 days of BM implant in rabbits, heterotopic bone formation occurred in 83.3% of control animals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of these models have variable repeatability, but the implantation of bone marrow to induce heterotopic bone formation can be demonstrated simply without the demand of time needed to prepare the material to be deployed. The induction procedure used in the present study was adopted from studies (5,10,11) that have documented that 35 days are sufficient for heterotopic bone formation in the quadriceps of rabbits following implantation of 2 mL BM collected from the iliac crest of the animal. Namazi and Mozaffarian (5) observed that after 35 days of BM implant in rabbits, heterotopic bone formation occurred in 83.3% of control animals.…”
Section: Discussionmentioning
confidence: 99%
“…The induction procedure used in the present study was adopted from studies (5,10,11) that have documented that 35 days are sufficient for heterotopic bone formation in the quadriceps of rabbits following implantation of 2 mL BM collected from the iliac crest of the animal. Namazi and Mozaffarian (5) observed that after 35 days of BM implant in rabbits, heterotopic bone formation occurred in 83.3% of control animals. Dudkiewicz et al (11), using the same methodology for HO induction, observed 97% heterotopic bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations